Pengaruh Pengembangan Karir dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawa PT Silverindo Djaya Lestari - Fransiska Alvianti Bali; Joko Ariawan (Pusat Riset dan Inovasi Nasional, 2025)
A retail company is a company that sells goods or services directly to the end consumer. The success of a retail company is highly dependent on employee satisfaction which if employee satisfaction is met, work productivity will be effective so that it can encourage the company to achieve its goals. However, if employee satisfaction is not met, it will cause poor productivity so that it can have an impact on the company's achievements. This study aims to analyze and determine the influence of career development and work environment on employee job satisfaction at PT Silverindo Djaya Lestari. The study used a statistical quantitative method with a sample of 43 employees. The independent variables in this study are career development and work environment, while the dependent variable is employee job satisfaction. The results of this study show that partially career development has a positive and significant effect on employee job satisfaction with a tcal value of 4,575 t table 2,021 and a sig value of 0.000<0.05, and the work environment also has a positive and significant effect on employee job satisfaction with a tcal value of 2,343>t table 2,021 and a sig value of 0.024<0.05. And simultaneously career development and work environment have a positive and significant effect on employee job satisfaction with a fcal value of 31,783>f table 4,085 and a sig value of 0.000<0.05.